2014
DOI: 10.1021/jo501781b
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Force Field: Parametric Computations of Proton–Proton Coupling Constants in 1H NMR Spectra

Abstract: Spin-spin coupling constants in (1)H NMR carry a wealth of structural information and offer a powerful tool for deciphering molecular structures. However, accurate ab initio or DFT calculations of spin-spin coupling constants have been very challenging and expensive. Scaling of (easy) Fermi contacts, fc, especially in the context of recent findings by Bally and Rablen (Bally, T.; Rablen, P. R. J. Org. Chem. 2011, 76, 4818), offers a framework for achieving practical evaluation of spin-spin coupling constants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 52 publications
3
50
0
Order By: Relevance
“…While the main purpose of this Minireview is to promote and present all the quantum chemistry tools available to assist in the NMR elucidation process, there are other useful approaches that deserve to be mentioned. One of them is the calculation of coupling constants ( J ) using quantum chemistry methods,, which have proven to be extremely useful to explore the conformational and stereochemical space of organic molecules . Other important methods that must be highlighted are the non‐quantum tools for structural assignment.…”
Section: Introductionmentioning
confidence: 99%
“…While the main purpose of this Minireview is to promote and present all the quantum chemistry tools available to assist in the NMR elucidation process, there are other useful approaches that deserve to be mentioned. One of them is the calculation of coupling constants ( J ) using quantum chemistry methods,, which have proven to be extremely useful to explore the conformational and stereochemical space of organic molecules . Other important methods that must be highlighted are the non‐quantum tools for structural assignment.…”
Section: Introductionmentioning
confidence: 99%
“…For aldehyde-based precursors 1a–1c the sole syn -diastereomer was observed, where “ syn ” refers to the relative position of the benzylic OH and the newly formed cyclohexadiene ring. The stereochemical assignment was based on the analysis of proton spin-spin coupling constants (SSCC) and their comparison with the values calculated with our relativistic force field (rff), DU8c , method, 19 Table S1.…”
mentioning
confidence: 99%
“…In order to shed light to the real structure of aldingenin C, the authors searched similar 13 C NMR data from the literature using the canonical representation of stereochemistry (CAST)/CNMR system and found that caespitol, a dibromo monochlorinated metabolite isolated from Laurencia caespitosa, displayed identical as aldingenin C was reported to have a molecular ion at m/z 332.0971 in the high-resolution electron ionization mass spectrometry (HREIMS) (corresponding to a formula C 15 74 reported on a fast and more precise parametrization approach to calculate coupling constants in the 1 H NMR spectra and after computationally analyze the spectrum of aldingenin A, these authors suggested that there is no oxabicyclo[2.2.1] heptane moiety in the structure of the natural compound. In the following year, the same group reinvestigated the structures of aldingenins A and B through computational studies, based primarily on proton spin-spin coupling constants (but also including 13 C NMR chemical shifts).…”
Section: Aldingeninsmentioning
confidence: 99%